Integrating Ecological Values, Environmental Education, and Sustainable Economic Behavior on Environmental Performance - Sri Muljaningsih; Silvi Asna Prestianawati; Eka Kusdiandra W (Jurnal Informatika Ekonomi Bisnis, 2026)
Improving environmental quality requires the integration of ecological values, environmental education, and sustainable economic behavior. However, the relationships among these components have not been widely examined in an integrated manner within the context of community-based empowerment. This study aims to develop an integrative model and validate it through a study at the Environmental Education Center Seloliman. The study employs a Sequential Exploratory Mixed Method approach that combines a Systematic Literature Review of 45 scientific articles based on the PRISMA 2020 guidelines and a Focus Group Discussion with managers, academics, village government, and the community. Data were analyzed using thematic coding and thematic synthesis. The results show that ecological values serve as the foundation for shaping sustainable economic behavior, while environmental education acts as a transformation mechanism that strengthens changes in community behavior. Empirical validation shows that community-based learning encourages the adoption of environmentally friendly practices and contributes to improved environmental performance. This study produces an integrative model that can serve as a basis for developing environmental education and community empowerment policies to support sustainable development.